PROGRAM COMPLEX FOR ANALYSIS AND TREATMENT ECHO-PULSE IMAGES - Stepanenko О. О.; Piza, D. M. (Radio Electronics, Computer Science, Control, 2012)
On the basis of analysis of methods of processing of echopulse images the lacks of existent approaches were educed and two new methods are offered. Worked out methods and programmatic system which is based on them, allow to promote efficiency of visual analysis medical and seismic ultrasonic images.